Ammonia-Oxidizing Archaea and Bacteria Differentially Contribute to Ammonia Oxidation in Sediments from Adjacent Waters of Rushan Bay, China - He, Hui; Zhen, Yu; Mi, Tiezhu; Fu, Lulu; Yu, Zhigang (Frontiers in Microbiology, 2018)
Ammonia oxidation plays a significant role in the nitrogen cycle in marine sediments. Ammonia-oxidizing archaea (AOA) and bacteria (AOB) are the key contributors to ammonia oxidation, and their relative contribution to this process is one of the most important issues related to the nitrogen cycle in the ocean. In this study, the differential contributions of AOA and AOB to ammonia oxidation in surface sediments from adjacent waters of Rushan Bay were studied based on the ammonia monooxygenase (amoA) gene. Molecular biology techniques were used to analyze ammonia oxidizers’ community characteristics, and potential nitrification incubation was applied to understand the ammonia oxidizers’ community activity. The objective was to determine the community structure and activity of AOA and AOB in surface sediments from adjacent waters of Rushan Bay and to discuss the different contributions of AOA and AOB to ammonia oxidation during summer and winter seasons in the studied area. Pyrosequencing analysis revealed that the diversity of AOA was higher than that of AOB. The majority of AOA and AOB clustered into Nitrosopumilus and Nitrosospira, respectively, indicating that the Nitrosopumilus group and Nitrosospira groups may be more adaptable in studied sediments. The AOA community was closely correlated to temperature, salinity and ammonium concentration, whereas the AOB community showed a stronger correlation with temperature, chlorophyll-a content (chla) and nitrite concentration. qPCR results showed that both the abundance and the transcript abundance of AOA was consistently greater than that of AOB. AOA and AOB differentially contributed to ammonia oxidation in different seasons. AOB occupied the dominant position in mediating ammonia oxidation during summer, while AOA might play a dominant role in ammonia oxidation during winter.